2010
DOI: 10.1103/physreve.81.041701
|View full text |Cite
|
Sign up to set email alerts
|

Elastic interaction between colloidal particles in confined nematic liquid crystals

Abstract: The theory of elastic interaction of micron size axially symmetric colloidal particles immersed into confined nematic liquid crystal has been proposed. General formulas are obtained for the self energy of one colloidal particle and interaction energy between two particles in arbitrary confined NLC with strong anchoring condition on the bounding surface. Particular cases of dipole-dipole interaction in the homeotropic and planar nematic cell with thickness L are considered and found to be exponentially screened… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…Simple analytical expressions for density perturbation and dissipative forces for the ensemble of widely separated small obstacles can be obtained using the qualitative approach described in Appendix A. This approach is similar to that based on the method of molecular field that was used to describe the elastic interaction of colloidal particles in a liquid crystal, see [58]. In particular, the gas density perturbation far from an isolated obstacle can be written as…”
Section: A the Asymptotic Behavior Of Density Perturbations And Dissmentioning
confidence: 99%
See 2 more Smart Citations
“…Simple analytical expressions for density perturbation and dissipative forces for the ensemble of widely separated small obstacles can be obtained using the qualitative approach described in Appendix A. This approach is similar to that based on the method of molecular field that was used to describe the elastic interaction of colloidal particles in a liquid crystal, see [58]. In particular, the gas density perturbation far from an isolated obstacle can be written as…”
Section: A the Asymptotic Behavior Of Density Perturbations And Dissmentioning
confidence: 99%
“…The latter means that the interaction between two inclusions cannot be separated out of the influence of all other inclusions. This is a general property of a nonlinear response or nonlinear systems, see [58]. The employed approach allows one to consider the non-linear response and to represent expressions for δn and f kj in the form similar to that given by the linear response for moving probe-particles (cf.…”
Section: A the Asymptotic Behavior Of Density Perturbations And Dissmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective interaction potential between two dipolar particles was also directly measured as a function of their separation d [61]. However, the accuracy of the measurements did not make it possible to compare them to the theoretical predictions, which concluded that the dipole-dipole power law of d −3 is exponentially screened for distances larger than the thickness of the cell, with an extended crossover region between the two regimes [103].…”
Section: Quasi Two-dimensional Nematic Colloidsmentioning
confidence: 99%
“…where U ij is the pair interaction energy between the i-th and j-th particles and U i +U pattern i is the one-particle energy. Both U ij and U i arise from the bulk and zero boundary conditions n µ (s) = 0 at the surfaces Σ and were discussed earlier in [20,21]. The last summand U pattern i originates from non-zero patterns n µ (s) = 0 at the surfaces Σ…”
mentioning
confidence: 81%